Prevalence of depression among students at a Sri Lankan University: A study using the Patient Health Questionnaire-9 (PHQ-9) during the COVID-19 pandemic - Ayanthi Wickramasinghe; Birgitta Essén; Rajendra Surenthirakumaran; Pia Axemo (BMC, 2023)
Abstract Background The prevalence of mental health disorders is known to be high among university students globally. Currently there are only a few studies on depression among university students in Sri Lanka. The aim of this study was to screen for the prevalence of Major Depressive Disorder (MDD) and other forms of depression, and to evaluate the factors associated with MDD. Methods A cross sectional survey using the Patient Health Questionnaire (PHQ-9) was conducted among 637, second-year students from the faculties of Management Studies & Commerce, Science and Medicine at the University of Jaffna, during the Coronavirus (COVID-19) pandemic. Bivariate associations were assessed using chi-squared tests. Logistic regression was used to evaluate factors associated with any type of ragging. Results MDD was considered to have been experienced by 31% of the students. From all three faculties, 70% of the students claimed to have experienced some form of depression ranging from mild to severe. The factor associated with MDD was the students' ethnicity. Conclusion Due to the high MDD risk among university students, it is imperative to develop psychosocial interventions to ensure early detection of mental health disorders and provide adequate support to safeguard this vulnerable population.